Public Spending on Human Capital and Economic Growth in Morocco - Elkhalfi, Oussama; Chaabita, Rachid; Zahraoui, Kamal; El Alaoui, Hicham (International Journal of Economics and Financial Issues, 2023)
The purpose of this paper is to measure the impact of public spending on human capital on economic growth in Morocco. The data cover the period between 1990 and 2019. Through the ARDL estimation model that is more appropriate to the structure of our data, the results reveal that human capital spending is conducive to economic growth in the current year and less conducive in subsequent years. Human capital spending in the long run has a beneficial effect on economic growth in Morocco and the effect is more severe for health spending than education spending. In view of these results, economic policies must support the administration of human capital expenditures towards investment expenditures in the education and health sector.